2013
DOI: 10.1001/jamaoto.2013.1074
|View full text |Cite
|
Sign up to set email alerts
|

Functional Swallowing Outcomes Following Transoral Robotic Surgery vs Primary Chemoradiotherapy in Patients With Advanced-Stage Oropharynx and Supraglottis Cancers

Abstract: Advanced-stage oropharynx and supraglottis cancers managed by transoral robotic surgery with adjuvant therapy resulted in significantly better swallowing MDADI outcomes at the follow-up visits at 6 and 12 months compared with tumors treated by primary chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(121 citation statements)
references
References 18 publications
9
110
0
2
Order By: Relevance
“…All were single-institution case series (level 4 evidence). Three studies reported on TORS for advanced (III–IV), 11,14,17 nd one reported outcomes for early (T1–T2) OPC tumors. 10 The remaining 8 studies reported outcomes after TORS for all stages of disease (AJCC I–IV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All were single-institution case series (level 4 evidence). Three studies reported on TORS for advanced (III–IV), 11,14,17 nd one reported outcomes for early (T1–T2) OPC tumors. 10 The remaining 8 studies reported outcomes after TORS for all stages of disease (AJCC I–IV).…”
Section: Resultsmentioning
confidence: 99%
“…Rates of perioperative feeding tube placement varied widely by disease stage and institutional practices (3% to 100%), and the average duration of perioperative nasogastric tubes was 2 to 13 days. 11,13,17,18 Excluding prophylactic placement, 15 18% to 39% of patients required gastrostomy placement, typically during adjuvant therapy. A single study of radical tonsillectomy reported the placement of gastrostomy tubes intraoperatively in all patients.…”
Section: Resultsmentioning
confidence: 99%
“…Our study population mainly consisted of HNC patients with stage IV diseases (.80%) who went through concurrent CRT with high-dose radiation (70 Gy), thus representing a very advanced HNC population. Recent studies suggest that this population of HNC patients do not exhibit significant improvement in MDADI scores at 12 months after CRT [14,15,22,23]. This contrasts with longer-term observations of less advanced patients, among whom improvements have been reported after 22 months [12].…”
Section: Discussionmentioning
confidence: 95%
“…It has been used in a number of prior studies [12][13][14] and characterizes how patients view their swallowing ability as a result of treatment and how the swallowing dysfunction affects their QOL. The MDADI has been used to track the longitudinal course of individual patient's outcomes [14,15]. The MDADI has four subscales--global, emotional, physical, and functional--to characterize the effects of dysphagia on different aspects of QOL.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…This score compared favorably with reports in the literature evaluating the MDADI in OPSCC patients treated with CRT [39]. A prospective non-randomized trial by More et al [40] compared the MDADI between patients with advanced stage OPSCC and supraglottic cancers following either TORS or CRT and found that there was no difference in the mean MDADI scores between the groups 3 months post-treatment, but that there was a difference at 6 months and 1 year. The TORS group had a significantly better mean MDADI score at 6 months and returned to baseline (78) at 1 year, whereas the CRT group fell from a baseline of 78 but only recovered to a mean score of 60.…”
Section: Functional Outcomesmentioning
confidence: 55%